(untitled) (Psychology Travelogs, 2021)
The article presents the understanding of motherhood as a multicomponent psychological phenomenon, which has physiological mechanisms, evolutionary history, cultural and individual features. Motherhood is not provided by fully innate mechanisms, it involves a biological desire for motherhood that is transformed by internalized social norms. At the present stage, motherhood is analyzed in terms of personal development of women, psychological and physiological characteristics of different periods of the reproductive cycle. Motherhood determines the unique situation of the development of a woman’s self-consciousness, which becomes a stage of rethinking the parental position based on her own childhood experience, a period of integration of the image of mother and child. The results of the study of psychological conditions that contribute to the successful development of the role of the mother after the birth of the first child have been experimentally obtained. The study involved 85 mothers who gave birth to their first child (children). Age of children – from 5 to 25 months. It was found that three groups of psychological conditions are important in the process of mastering the role of the mother: the level of rigidity of the woman, the justification of expectations about motherhood and the attitude to the components of this role (maternal functions, attitude to the role of mother and emotional attitude to the newborn). Mothers with a high level of rigidity rate the difficulty of adapting to the birth of a child as the highest. Those women whose expectations regarding motherhood have not been met have difficulty getting used to the changes that are associated with the birth of a child. Subjectively, they experience the abandonment of many spheres of life, forced isolation and focus on the child, the routine and routine of the first months of child care. Difficulties associated with caring for a newborn are more easily tolerated by women, with acceptance related to the components of the mother’s role: to herself in the role of the mother, maternal functions and to the child itself. Prospects for further research remain the factors influencing the formation of adequate expectations regarding motherhood.